The productive concentration as a determinant for credit offer in Latin America - Barriga, Nicolás (2020)
Credit, in Latin American countries, is used as a financing mechanism for new ventures, companies and industries, allowing the development of productive chains in the economy. At the same time, Latin American region has been characterized by maintaining a concentrated production in certain economic sectors. Therefore, this research aims to determine the relationship between productive concentration –measured through the Herfindahl-Hirschman index– and the acceleration of credit offer in Latin America. In order to achieve this goal, an econometric model of panel data was used for fifteen representative economies in the region, in the period 2004-2016. The main results of this research indicate that the productive concentration of Latin American economies slows the credit offer in this region.